THEMATIC EVOLUTION OF WORKPLACE INCLUSION: A BIBLIOMETRIC ANALYSIS OF EMPLOYEE AND MANAGEMENT PERSPECTIVES - Chauhan, Neeraj; Ahlawat, Pardeep K. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study use bibliometric and thematic analytic techniques to monitor the development of several subjects in the literature on workplace inclusion, as seen by managers and workers. The emphasis has shifted from just adhering to anti-discrimination rules to acknowledging the need of fostering inclusion within a heterogeneous workforce. This change is shown by noteworthy discoveries that unveil novel topics, alterations, and theoretical frameworks. The study's findings emphasise the significance of promoting an inclusive environment and demonstrate how these changing attitudes have a substantial impact on organisational innovation, employee involvement, and overall effectiveness.